Paradox of Choice: Apakah Terlalu Banyak Pilihan Produk di Platform Shopee Dapat Mempengaruhi Keputusan Pembelian Konsumsi - Reza Syakif Afendi; Raka Raka; Ramita Agustin; Rifki Adi Nugraha Sinurat; Agung Rizki Putra (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
In the era of rapidly developing e-commerce, one of which is the Shopee platform, consumers are often faced with a variety of seemingly unlimited product choices. The Paradox of Choice is a psychological phenomenon that explains how too many choices can cause confusion and dissatisfaction, even inhibiting purchasing decisions. The development of e-commerce has increased the number of product choices available to consumers. This study shows that too many choices can cause a paradox of choice, which can affect consumer decisions. This study aims to investigate the effect of the paradox of choice on consumption in e-commerce, especially Shopee. This article uses a quantitative research method that is strengthened by primary data based on the results of a questionnaire given to several respondents. The results of the study show that the paradox of choice can affect consumer decisions and reduce consumption. Therefore, this study concludes that e-commerce needs to develop strategies to reduce consumer cognitive load and improve the overall shopping experience.